Enantioselective Zirconium-catalyzed Transformations - Pellissier, Hélène (Current Organic Chemistry, 2024)
The cheaper and less-toxic metals of group 4 compared with common metals used in catalysis are increasingly applied in catalysis, resulting in the development of many novel greener transformations. Zirconium is abundant, non-toxic, and exhibits a remarkably diversified chemical reactivity among these metals. Since the first asymmetric zirconium-catalyzed reaction disclosed by Nugent in 1992, a wide variety of chiral zirconium catalysts have been proven to be capable of promoting many types of highly enantioselective transformations, spanning from standard reactions, such as Friedel-Crafts reactions, cycloadditions, aldol reactions, Mannich reactions, epoxidations, nucleophilic additions to carbonyl compounds and derivatives, cyanations, ring-opening reactions, hydroxylations, hydroformylations, carboaluminations among others, to more modern and complex domino and tandem processes. This review aims to collect the major progress achieved in the field of enantioselective transformations of all types promoted by chiral zirconium catalysts, covering the literature since the beginning of 2003 and illustrating the power of these non-toxic catalysts to provide high enantioselectivity in almost all kinds of asymmetric organic reactions. It is divided into ten parts, focussing consecutively on enantioselective Friedel-Crafts reactions, cycloadditions, aldol reactions, Mannich reactions, epoxidations, additions of alkylzinc reagents to imines, cyanations, ring-opening reactions, hydroxylations, and domino/ tandem reactions. The diversity of these transformations well reflects that of the products synthesized. For example, chiral indole and pyrrole derivatives were prepared from Friedel-Crafts reactions; pyranones, pyridones and pyrazolidines from cycloadditions; β-hydroxy α-diazo carbonyl compounds, β- hydroxy (thio)esters and β-hydroxy-α-amino acid derivatives from aldol reactions; β-amino (thio)esters from Mannich reactions; functionalized epoxides from epoxidations; amines from additions of alkylzinc reagents to imines; amino nitriles from cyanations; 1,2-diamines and β-vinyloxy alcohols from ring-opening processes; 2- hydroxy 1-indanones from hydroxylations; various amines, 1,3-anti-diol monoesters, β-amino esters, α,β- dihydroxy acid derivatives, α-amino ketones, indoles, cyclopentane and aryl α-aminophosphonates from domino/ tandem reactions. Furthermore, the utility of these novel methodologies was demonstrated in the total synthesis of numerous essential bioactive products, such as (+)-prelactone C, (+)-9-deoxygoniopypyrone, (+)- coniine, vancomycin, (+)-fusarisetin A, mycolipenic acid, onchidin, indoxacarb, tachykinin receptor antagonists, cerebroprotecting agent MS-153, and L-erythro-sphingosine. The advances achieved in the last three decades demonstrate that the non-toxicity, abundance, and efficiency of zirconium make its application in catalysis suiting the growing demand for more environmentally benign processes, offering the real opportunity to replace other toxic and expensive metals in the near future.
Keywords: transition metals